Relationship between Civic Sense and Civic Responsibility of Junior High School Students - Pandey, Chandra Prabha; Rathore, H.C.S. (JOURNAL OF INDIAN EDUCATION, 2016)
The inference of this study, which explored the relationship between civic sense and civic responsibility of junior high school students, is based on the findings of a survey. The sample consisted of 121 students (62 girls and 59 boys) of 8th grade at CBSE schools of Varanasi district, UP. The prominent questions of the study were: (a) what is the relationship between students’ civic sense and civic responsibility?, and (b) does the relationship between civic sense and civic responsibility differ with gender? Self-developed civic sense test and civic responsibility scale have been used for collection of the data. Product moment coefficient of correlation r and t ratio was calculated to analyse the data. The result of the study revealed no significant relationship between students’ civic sense and their civic responsibility. On the basis of the findings, it concluded that a student who possesses a high level of civic sense may not be civic responsible. The results also show no significant difference between girls and boys on civic sense test. However, girls outscore boys on the graph of civic responsibility. Girls having equal level of civic sense are more responsible in comparison to boys of the same age group.